Practical experiences of a designing and operating a pilot aquaponic system - Csorvási, Éva; Juhász, Péter; Fehér, Milán; Nemes, Ildikó; Stündl, László; Takácsné Hájos, Mária; Bársony, Péter (Acta Agraria Debreceniensis, 2014)
Aquaponics is the combination of fish farming (aquaculture) and the soilless cultivation of plants (hydroponics). The aquaponics system is an artificial, recirculating ecosystem, in which bacterial processes convert the waste materials in the water used for fish rearing into plant nutrients, and therefore with the generated heat it is suitable for culturing economically valuable plants, and thus it mitigates the nutrient laden and quantity of the intensive fish producing systems’ effluent water.The primary goal of our 12 separate unit’s aquaponics system was to gain experience. We would like to find the right plant species, which are fit for that medium, and their crop can be sold. Besides the plants, our attention focused on the fish. Two fish species were included in the experiments, the common carp and barramundi. It was difficult to create them a perfect living space, besides a constantly changing conditions temperature. Apart the above mentioned we had a problem with the number of individuals per tank, the deformity of the fish body and the too high volume of pH (we registered continuous values above 8.4). We get by carps 4.7 grams of weight gain during 15 weeks, because of the bad conditions.The main problems at the plants are caused by aphesis and protection against sunburn. Even so we have got the multiples of field yields for each plant species. At salad has grown twice of field yields, tomatoes one and half, kohlrabi than 3.5 times more. The causes of multiple yields are the continuous balanced water and the nutrient uptake of plants. Each plant species fit for cultivating in aquaponics and their crops are delicious, chemical -free, safe and marketable. The plants should be more concentrated. After the experiment, it has been determinated that the carp is suitable for aquaponics, but greater weight gain could be achieved with optimal selection of size of rearing units.